2018
DOI: 10.1080/2162402x.2018.1456612
|View full text |Cite
|
Sign up to set email alerts
|

The role of Foxp3 and Tbet co-expressing Treg cells in lung carcinoma

Abstract: Despite the opposite roles of Tbet and Foxp3 in the immune system as well as in tumour biology, recent studies have demonstrated the presence of of CD4 T cells, expressing both, Tbet and Foxp3. Although TbetFoxp3 T cells are currently a subject of intense research, less is known about their biological function especially in cancer. Here we found a considerable accumulation of TbetFoxp3CD4 T cells, mediated by the immunosuppressive cytokine TGFβ in the lungs of tumour bearing mice. This is in line with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…9,10 However, the type of TI-Tregs may vary in different cancers and patients, as Th1-like Tregs, defined by the expression of T-bet, made up 40% of Foxp3 + cells in a murine model of lung carcinoma, and between 2% and 10% of Tregs from human nonsmall cell lung carcinomas. 42 CXCR3, the Th1-defining chemokine receptor, was the most prevalent chemokine receptor on tumour-infiltrating FOXP3 + Treg in human ovarian cancers. 43 Because Th1-like TI-Tregs may best inhibit Th1 effector T-cell responses that are associated with cytotoxic CD8 + T-cells and IFN-c production, selectively eliminating these Tregs may have the greatest effect on potentiating the most effective type of anti-tumour Tcell responses.…”
Section: Chemokine Receptorsmentioning
confidence: 97%
See 1 more Smart Citation
“…9,10 However, the type of TI-Tregs may vary in different cancers and patients, as Th1-like Tregs, defined by the expression of T-bet, made up 40% of Foxp3 + cells in a murine model of lung carcinoma, and between 2% and 10% of Tregs from human nonsmall cell lung carcinomas. 42 CXCR3, the Th1-defining chemokine receptor, was the most prevalent chemokine receptor on tumour-infiltrating FOXP3 + Treg in human ovarian cancers. 43 Because Th1-like TI-Tregs may best inhibit Th1 effector T-cell responses that are associated with cytotoxic CD8 + T-cells and IFN-c production, selectively eliminating these Tregs may have the greatest effect on potentiating the most effective type of anti-tumour Tcell responses.…”
Section: Chemokine Receptorsmentioning
confidence: 97%
“…CCR8, another chemokine receptor associated with Th2 cells, may prove to be a superior target, as it was found highly expressed on TI‐Tregs in multiple solid tumours, but in a more restricted fashion than CCR4 . However, the type of TI‐Tregs may vary in different cancers and patients, as Th1‐like Tregs, defined by the expression of T‐bet, made up 40% of Foxp3 + cells in a murine model of lung carcinoma, and between 2% and 10% of Tregs from human non‐small cell lung carcinomas . CXCR3, the Th1‐defining chemokine receptor, was the most prevalent chemokine receptor on tumour‐infiltrating FOXP3 + Treg in human ovarian cancers .…”
Section: Activation and Differentiation Of Ti‐tregsmentioning
confidence: 99%
“…Tumour‐infiltrating Treg cells have been widely reported to up‐regulate T helper lineage transcription factors, especially T‐bet, and in some cases GATA‐3 . Both T‐bet‐expressing and GATA‐3‐expressing Treg cells were shown to have enhanced suppression of anti‐tumour CD8 + T cells, without up‐regulating inflammatory cytokines characteristic of their Foxp3 − counterparts.…”
Section: Pi3kδ In Cytokine‐driven Adaptation In Tumour Treg Cellsmentioning
confidence: 99%
“…127,128 Tumour-infiltrating Treg cells have been widely reported to up-regulate T helper lineage transcription factors, especially T-bet, and in some cases GATA-3. [129][130][131] Both T-bet-expressing and GATA-3-expressing Treg cells were shown to have enhanced suppression of anti-tumour CD8 + T cells, without up-regulating inflammatory cytokines characteristic of their Foxp3 À counterparts. Strikingly, Treg cells have been reported to rely on granzyme expression in mediating tumour immunosuppression 132,133 but not in the control of graft-versus-host disease, 134 and it is plausible that an adaptive Th1-like transcriptional programme driven by the expression of T-bet is required for the manifestation of these context-specific suppressive features.…”
Section: Pi3kd In Cytokine-driven Adaptation In Tumour Treg Cellsmentioning
confidence: 99%
“…Recent studies demonstrated that CD4 + T cells expressing both, T-bet and FoxP3, exert regulatory rather than pro-inflammatory functions. T-bet is required for the expansion of these immunosuppressive cells to limit Th1-mediated immune responses [51,52]. We hypothesized this subset might be involved in pathogen-specific loss of host resistance.…”
Section: Discussionmentioning
confidence: 99%